Anatomical changes during early gonad development in the protogynous greasy grouper Epinephelus tauvina (Forsskal) - Grace, Mathew; Kuruvilla, Mathew (Indian Journal of Fisheries, 2016)
Anatomical changes during early gonad development of the culturable species of grouper Epinephelus tauvina was studied. All juveniles developed an ovarian phase initially followed by the bisexual phase gonad. Bisexual phase gonad occurred when the fish was around two years old and in the length range of 188-380 mm total length. The minimum size at first sexual maturation for females was 380 mm total length at an age of two and a half years. The presence of bisexual phase and spermatogenic cysts in juvenile gonads in E. tauvina could be an indication of primary male differentiation. Based on gonadal histological study of E. tauvina till first sexual maturation, it was found that all the juveniles developed an ovarian structure initially and subsequently developed a bisexual phase with male tissue scattered among lamellae, prior to first sexual maturation as females. Although it was not possible to find any primary males among fishes collected from the wild, the developmental significance of a bisexual phase in E. tauvina juveniles is assumed to be similar to diandric protogynous species, having secondary males as well as primary males developed directly from juveniles through sexual differentian.